Design and Application of Electromechanical Control System Based on Computer Fault Tolerance Technology. (5th October 2022) - Wei, Rui
Abstract : In order to improve the stability and control effect of the electromechanical control system, this paper designs the electromechanical control system combined with the computer fault-tolerant technology and proposes an electromechanical control signal processing algorithm. In order to improve the accuracy of the path loss calculation, according to Fresnel's law, this paper deduces the expression of the reflection coefficient of electromechanical control signal with the distance between the transmitting antenna and the receiving antenna as the main variable and then compares the path loss with the ground and the ceiling as the reflecting surface. In addition, in order to study the path loss, this paper selects different reflective materials to study their path loss under horizontal polarization and vertical polarization. The results show that under the vertical polarization, the path loss fluctuation is not large, and the agreement is higher than that of the horizontal polarization. The research results show that the electromechanical control system based on computer fault-tolerance technology proposed in this paper has stable performance and can play an important role in the control of electromechanical systems.